The Ebola crisis and people with disabilities' access to healthcare and government services in Liberia - Maria Kett; Ellie Cole; Lucila Beato; Mark Carew; Richard Ngafuan; Sekkoh Konneh; Tim Colbourn (BMC, 2021)
Abstract Background There has been little research on the impact of the 2014-2015 West African Ebola crisis on people with disabilities. This paper outlines the way in which the Ebola Virus Disease (EVD) outbreak in Liberia in 2015 highlighted existing inequalities and exclusion of people with disabilities and their households. Methods The results presented here are part of a larger ESRC/DFID-funded mixed methods research project in Liberia (2014-2017) which included a quantitative household survey undertaken in five counties, complemented by qualitative focus group discussions and interviews with people with disabilities and other key stakeholders. Uniquely, this research gathered information about people with disabilities' experience of the EVD outbreak, as well as additional socioeconomic and inclusion data, that compared their experience with non-disabled community members. Results Reflections by people with disabilities themselves show knowledge, preparation, and responses to the EVD epidemic was often markedly different among people with disabilities due to limited resources, lack of inclusion by many mainstream public health and medical interventions and pre-existing discrimination, marginalisation and exclusion. Interviews with other key stakeholder revealed a lack of awareness of disability issues or sufficient training to include this population systematically in both Ebola response activities and general health services. Key findings include the need to understand and mitigate direct and indirect health consequences of unequal responses to the epidemic, as well as the limited capacity of healthcare and social services to respond to people with disabilities. Conclusion There are lessons to be learned from Ebola outbreak around inclusion of people with disabilities, relevant to the current COVID-19 pandemic. Now is the time to undertake measures to ensure that people with disabilities do not continue to be marginalised and excluded during global public health emergencies.